2016
DOI: 10.1371/journal.pone.0156869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recurrent Selection on Drought Tolerance and Related Morpho-Physiological Traits in Bread Wheat

Abstract: Drought is one of the major abiotic stresses affecting wheat yield. A recurrent selection program was conducted to improve the drought tolerance and yield of bread wheat using drought tolerant advanced breeding lines from a drought tolerant x susceptible cross (HI 1500 x HUW 510). The parental lines were evaluated for yield, biomass and harvest index (HI) in addition to the drought adaptive traits like Canopy Temperature (CT), chlorophyll content and Normalized Difference Vegetative Index (NDVI). After three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 53 publications
1
18
0
2
Order By: Relevance
“…As expected, grain-filling stages appeared the most valuable for detecting NDVI-related genetic differences among genotypes (61.2% of which were identified at the grain-filling stage) in response to the progressive onset of senescence and drought stress related to the water-shortage treatment. Along this line, breeding strategies for enhancing drought tolerance are increasingly adopting remote-sensing of NDVI and other spectral technologies (Monneveux et al, 2012 ; Araus and Cairns, 2014 ; Ramya et al, 2016 ; Trapp et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, grain-filling stages appeared the most valuable for detecting NDVI-related genetic differences among genotypes (61.2% of which were identified at the grain-filling stage) in response to the progressive onset of senescence and drought stress related to the water-shortage treatment. Along this line, breeding strategies for enhancing drought tolerance are increasingly adopting remote-sensing of NDVI and other spectral technologies (Monneveux et al, 2012 ; Araus and Cairns, 2014 ; Ramya et al, 2016 ; Trapp et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, this method is a procedure of collecting the desired characters of a combination crosses with some continuously crossing selected segregants in order to obtain better population than previous ones, due to the plants have a combination of desired characters. Reference [11] reported that recurrent selection in Wheat Bread plants could identify potential lines with high yield and drought stress tolerant for limited water resource areas. Recurrent selection techniques have also been carried out by [12] with 8 cycles to genetically estimate the progress yield of a chickpea.…”
Section: Introductionmentioning
confidence: 99%
“…Based on grouping the number of tillers [20], the number of productive tillers in Bugis/IR7858-1 ranged from 2.0-21.0, whereas Bugis/IR148 had 1.0-17.0 (Table 4). Therefore, population of lines derived Bugis/IR7858-1 more dominant being moderate to high, and can be grouped into 62 medium productivity lines (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and 59 high productivity lines (> 19), whereas those 140 genotypes derived from Bugis/IR148 had 52 very low productivity lines (<5) and two had low productivity lines (5-9) (Table 4). The number of productive tillers in genotype results of crossing Sriwijaya/IR148 and Sriwijaya/IR7858-1 more dominant in low to medium productivity lines (Table 4).…”
Section: B Agronomy Characters Of Upland Rice Population Crosses Srimentioning
confidence: 99%
“…The result lines of the RS method from B11742 crossing combination produced plant segregate which has new plant type and resistance to leaf blight disease and better quality of rice [14]. Newest reported by [15] that the effect of recurrent selection on drought tolerance also identified potential lines with high yield and drought tolerance for subsequent varietal development for limited water areas in Breat Wheat.…”
Section: Introductionmentioning
confidence: 99%